A CLIL Experience Based on the Use of Tasks and Different Genre Types - Ana María Cendoya; María Verónica Di Bin (Universidad de La Sabana, 2010)
Teaching English in the 21st century poses the challenge of facing and adapting to the new status of the English language as a lingua franca. Accordingly, its teaching methodology and didactics have changed too. It is in this context that a new methodology Content and Language Integrated Learning (CLIL) has appeared. This paper aims to point out what the core features of CLIL methodology are and how task-based and genre-based pedagogies can complement it. It then presents the analysis of a classroom experience in order to show how problem solving tasks can help enhance CLIL contexts so that students can develop their linguistic competence as well as their content knowledge in English by means of reading, interpreting, and producing texts of different genre types.